Public Policies: Discussions About their Analysis and Evaluation (Andamios, Revista de Investigación Social, 2013)
The article analyses the most important discussions in  theoretical and empirical public policies with regards to different approaches, methods and research techniques used in two relevant stages of their process: ex-ante analysis and ex-post evaluation. It concludes that different weaknesses, such as, extremely simplified processes that only focus on economics and that neglect qualitative information, justify the limited use of the analysis in the decisionmaking process. In evaluation matter, it recognizes relevant progress in two different approaches (constructivism and positivism). It argues in favor of the latter because it shows more comprehension on the complexity of the public policies, and it demonstrates more interest in social participation, interdisciplinary studies and the combination of qualitative and quantitative methods.
Keywords: Public policies; analysis evaluation; methods; Mexico